Microclimatic characterization of tourist caves in Parque Nacional Cavernas do Peruaçu, Minas Gerais, Brazil - Gomes, Mauro; Santos, Darcy José dos; Azevedo, Úrsula Ruchkys de; Travassos, Luiz Eduardo Panisset (Sociedade & Natureza, 2021)
The cave environment has very peculiar atmospheric conditions that directly influence the existence and maintenance of the set of biotic and abiotic, socioeconomic, and historical-cultural elements represented by the caves or associated with them. In caves where tourist activities are carried out, human presence can affect the delicate balance of these conditions. This research was developed to characterize the cave microclimate of seven caves that make up the tourist circuit of the Parque Nacional Cavernas do Peruaçu, located in the northern region of the State of Minas Gerais, in the southeastern region of Brazil. Temperature and relative humidity data were collected by 41 automated meters that accumulated just over 110,300 records each. The research stands out for being one of the only long-term (2017 to 2019) developed in the country. The analysis of this information allowed not only to characterize the microclimate of the caves, but also to observe the relationship of these attributes with the internal morphology and with the position that the caves are in relation to the region’s karst relief. The methodology developed by this research can subsidize the Environmental Conditions Monitoring Program of the Caves to be implemented by the management of the National Park and the identification of more sensitive environments inside the caves will allow the reorganization of the visitation to these attractions.